Tuberculosis in slaughtered cattle and workers in some abattoirs of Baghdad governorate. (December 2016) - AL-Thwani, A.N.; AL-Mashhadani, M.S.
Abstract: Objective/background: Tuberculosis (the white plague) is regarded as one of the most widespread infectious diseases and continues to be a leading cause of death and the most prominent public health problem worldwide. It is caused by Mycobacterium tuberculosis complex, which refers to a group of seven species; one of them known as Mycobacterium bovis —the cause of bovine-type tuberculosis—has an exceptionally wide host range. It infects cattle, humans, goats, cats, dogs, buffalo, and deer. Many susceptible species, including man, are spillover hosts in which infection is not self-maintaining. The objective of this study is to investigate the role of infected slaughtered cattle in spreading tuberculosis to those who work in abattoirs. Methods: Three hundred slaughter cattle in some abattoirs of the Baghdad governorate were examined grossly. Tissue samples were taken from lesions that had appeared on lymph nodes, lung, liver, spleen, peritoium, and intestines. A routine examination was performed: (1) smear for Ziehl Neelsen acid-fast stain; (2) cultured: each sample was cultured on Stone-brink with sodium pyrovite and on Lowenstein media which contain glycerol; and (3) incubated at 37 °C for 4–10 weeks, to observe the characteristic features of bacterial colonies. Biochemical tests, nitrate reduction, urea analysis, tween 80 lysis, and catalase test were employed to isolate and identify the bacteria. Pieces from tissue samples were kept in 10% formalin for histopathological investigation. Tuberculin tests and X-rays were conducted for 186 workers who were in contact with slaughtered cattle in the same abattoirs, with an age range of 15 years to 60 years. Sputum samples were collected from all workers in clean and sterile containers, and subjected to the same routine examination. The collection of samples was carried out under strict and sterile conditions and the sputum was kept in 50% oxalic acid for 20 min before culture on media to avoid the contamination. Results: Gross examination of cattle carcasses showed tubercle in four of them that was distributed in lymph nodes and different organs especially in lungs, livers, and in one case tubercle appeared on the peritoneum and intestines. A histopathological study revealed different lesions with an accumulation of lymphocytes and macrophages in lymph nodes and organs. Four isolates of M. bovis were diagnosed and identified by routine examination that indicated the percentage of infection in slaughtered cattle was 1.33%. The result of the workers' examinations clarified that only one of the workers had a positive result for the tuberculin test, whereas three of them had positive results in X-ray and routine examination. Three isolates were obtained from workers (1.6%); two of these isolates were diagnosed as M. bovis and the other as M. tuberculosis . Conclusion: The main conclusion of this study is that two workers were infected with cattle's strain which confirms the role of slaughtered cattle in the transmission of this dangerous, chronic, and zoonotic disease to man.